تأثير ضريبة القيمة المضافة على الاقتصاد في دولة الإمارات العربية المتحدة: The Effect of Value-Added Tax on the Economy of the United Arab Emirates - Hassan Abdulla, Ahmad Mohammad; Zakaria , Mohamad Zaharuddin (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص وتعتبر ضريبة القيمة المضافة حديثة، إذ تعد مصدراً أساسياً للموارد الحكومية، حيث تعتمد اقتصاديات الدول المتطورة عليها في أوربا واقتصاديات دول أمريكا اللاتينية بشكل كبير، وهي بذلك تعد عنصراً محورياً من عناصر النظام الضريبي لكل من الاقتصاد النامي والمتحول، حيث تتجه الأساليب الحديثة في التشريعات الضريبية نحو نقل عبء الضريبية من قطاعات انتاج الثروة لتضعه في قطاعات استعمالها، أي تخفيض الضرائب الواقعة على الدخل إلى زيادتها في الإنفاق. تطبق الضريبة على معظم المعاملات التي تتم على السلع والخدمات عدا الاستثناءات التي تقرها الهيئة الاتحادية للضرائب، ويتحمل عبئها المستهلك، ولذلك يمكن توقع ارتفاع كلفة المعيشة بشكل طفيف، ويختلف ذلك باختلاف نمط حياة الأفراد، وسلوكهم الإنفاقي. ولن تكون كل الشركات ملزمة بالتسجيل من أجل الضريبة، وإنما فقط تلك التي تزيد إيراداتها على الحد الأدنى للإيرادات. وقدمت الدراسة التوصيات الآتية: إعداد موارد بشرية كافية من أجل القيام بأعباء تطبيق ضريبة القيمة المضافة وحساباتها. وافتتاح معاهد محاسبة وأقسام جامعية تتعلق بأصول المحاسبة والضريبة لتوطين هذه المهن. وفتح الهيئة الاتحادية مكاتب لها أو فروع دائمة في أماكن حكومية مثل الدوائر الاقتصادية المحلية المعروفة من قبل التجار لتقديم خدماتها الاستشارية بشكل مباشر وشخصي، بما يدعم المشاريع الصغيرة ويجنبها الغرامة. Abstract The value-added tax is considered modern, as it is a major source of government resources, as the economies of developed countries in Europe and the economies of Latin American countries depend heavily on it, and thus it is a pivotal element of the tax system for both developing and transforming economies, where modern methods in tax legislation tend to Towards transferring the tax burden from the sectors of wealth production to place it in the sectors of their use, i.e. reducing taxes on income to increasing spending. The tax is applied to most transactions made on goods and services, except for the exceptions approved by the Federal Tax Authority, and the burden is borne by the consumer. Therefore, a slight increase in the cost of living can be expected, and this varies according to the lifestyle of individuals and their spending behavior. Not all companies will be required to register for the tax, only those whose revenue exceeds the revenue threshold. The study made the following recommendations: Preparing sufficient human resources in order to carry out the burdens of implementing the value-added tax and its calculations. And the opening of accounting institutes and university departments related to accounting and tax principles to localize these professions. The Federal Authority has opened offices for it or permanent branches in government places such as local economic departments known by traders to provide its advisory services directly and personally, in order to support small projects and avoid fines.